Pengembangan dan Integrasi Sistem Otomasi Perpustakaan Digital Berbasis INLISLite untuk Meningkatan Layanan Informasi di SMA Methodist 3 Palembang - Maria Ulfa; Ayu Andira; Evi Yulianingsih; Siti Sauda (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of information technology in the digital era has influenced various aspects of life, including library services. Along with these technological advancements, libraries are required to develop technology-based services through the implementation of digital library automation systems such as INLISLite to improve the quality of information services.This research was conducted at the library of SMA Methodist 3 Palembang, which still used a manual system for managing borrowing, returning, searching, and cataloging books. As a result, delays and data recording errors frequently occurred. In addition, unstructured data storage made library management less efficient. Therefore, the development and integration of an INLISLite-based digital library automation system were carried out to assist in managing book collections, member data, borrowing and returning transactions, fines, and library reports in a more effective and structured manner.The benefit of this research is to support the creation of a library that continuously adapts to technological developments and provides better services to its users. This study employed the Research and Development (R&D) method, consisting of data collection, planning, development, testing, and product refinement stages. The results of this research are expected to improve the effectiveness, efficiency, and quality of information services in the school library